Development of an analytical procedure to analyze microplastics in edible macroalgae using an enzymatic-oxidative digestion. (October 2022) - López-Rosales, Adrián; Andrade, Jose M.; López-Mahía, Purificación; Muniategui-Lorenzo, Soledad
Abstract: Besides being food and a refuge to marine species, macroalgae are a powerful and renewable economic resource. However, they may introduce microplastics (MPs) in the trophic chain. We developed a reliable analytical method to characterize and quantify MPs in common and edible macroalgae. Several digestion methods and filters, along with various measurement options, were studied. A new enzymatic-oxidative protocol with a unique final filtration was selected and validated with a mixture of 5 commercial macroalgae ( Undaria pinnatifida spp, Porphyra spp, Ulva spp, Laminaria ochroleuca and Himanthalia elongate ). Further, it was shown that washing the macroalgae to release MPs is suboptimal and the potential adhesion of MPs to macroalgae was evaluated. A filter subsampling strategy that scans 33.64 % of its surface reduced the time required to characterize <70 μm particles and fibres directly on the 47 mm diameter filter using an IR microscope (1 sample/day). Graphical abstract: Unlabelled Image Highlights: Plain washing of algae does not remove microplastics effectively. A mild enzymatic-oxidative digestion for edible seaweeds and macroalgae is proposed. A filter subsampling strategy to determine <70 μm fibres and particles is proposed. The filter subsampling strategy requires measuring 33.6 % of the filter.